Integrated potentiostat for neurotransmitter sensing. - Murari, K.
We have presented a chemical analysis paradigm for neurochemical studies, as opposed to the traditional electrophysiological regime. We described electrochemical analysis and the instrumentation involved in doing such analysis. The article presents the design and characterization of a 16-channel, high-sensitivity, wide-range VLSI potentiostat. We demonstrate the use of this potentiostat in real-time in vitro monitoring of the neurotransmitter dopamine.
Keywords: Chemical analysis; Electrochemical analysis; High-sensitivity wide-range VLSI potentiostat; Integrated potentiostat; Neurochemical studies; Neurotransmitter dopamine; Neurotransmitter sensing; Real-time in vitro monitoring